Strategies for Building A Competitive and Excellent Islamic Educational Institution - Maimun Maimun; Miftachul Huda; Muhammad Muhammad (POTENSIA: Jurnal Kependidikan Islam, 2022)
In the globalization era filled with competition, educational institutions were demanded to create a competitive advantage for their survival continuously. This article aims to explore the competitive advantage design in Islamic educational institutions and its strategies for managing the competitive advantage. This study applies a qualitative research design of multisite studies because it examines background or data storage on two subjects, i.e., MTs Alam Sayang Ibu Dasan Geriya and MTs Nurul Haramain NW Narmada West Lombok. This research result indicates that, variously, there are advantages at the two sites studied in the design and strategy of managing competitive advantage. Designing the competitive advantages of the two madrasahs, which became the research object, has similarities in the effort for considering a typical society as the stakeholders, considering technological development, managing the existing Human Resources in the madrasah, and managing the madrasah's infrastructure and facilities. Meanwhile, in managing the strategies for competitive advantage, apparently, they do not have conspicuous similarities, particularly in the content and objective wanted to be achieved by those madrasahs.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//